Kontekstualisasi Pemikiran Al-Farabi Menuju Indonesia yang Bahagia dan Negara Ideal - syamsiyani yani (JURNAL PENELITIAN KEISLAMAN, 2020)
The political upheaval that has been on display in Indonesia lately is increasingly showing the poor morality of society and the nation's civilization. Al-F?rabi invites politics to achieve the existence of peace and happiness, one of which is the ideal state or al-Madinah al-F?dilah. This is where the goal of presenting the figure of the Islamic philosopher, al-F?rabi as a very famous figure who is famous for his thought ‘ara Ahl al-M?dinah. The method used in this research is a descriptive qualitative library research approach. A descriptive approach is a research method that aims to develop a theory of thought or figure. The aim is to reveal the reality of al-F?rabi's thinking in accordance with the reality in the field, from al-F?rabi's political thinking is expected to create an advanced Indonesian state, a happy and ideal country, especially for universal community life.